Dinamika Sektor Informal dan Risiko Dibaliknya - Arif Nur Widyatama; Rofi Sri Utami; Siti Rahayu Estu Ningrum (Universitas 45 Surabaya, 2023)
This article discusses community groups working in the informal sector. The informal economic sector of the people of the coastal area which produces fish sacs. Work to make ends meet and depend on uncertain market demand. Working under the control of collectors who determine the amount of production and as a provider of capital for fish sack craftsmen. The power relations established by collectors determine the dynamics of the fish sack production process. This research uses qualitative methods with an ethnographic approach. Furthermore, researchers used the perspective of the Risk Society theory put forward by Ulrich Beck. With all the risks that must be put aside by the craftsmen in order to meet market demand for fish sacks, the craftsmen have always carried out the production process until now.